The Reception of the Phenomenon of Edith Stein: „Place of Action: Poland“ - Baaden, James (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2016)
The article shows the processes of reception of the person of Edith Stein in Germany, the Netherlands and Poland. According to the author, this reception could be divided into materials and processes. The first group includes impressions, opinions and interpretations. The second is formed, for instance, by beatification and canonisation documents. The author refers to Walter Benjamin and Hans-George Gadamer showing the dialogical elements of the reception process. Germany became the place where the reception of Edith Stein was the strongest due to its historical situation and the context of the ‘hearing’ of National Socialism as well as the role of the Catholic Church in the Third Reich. An alternative way of reception of Stein is exemplified by the Dutch town of Echt, which offered Edith Stein a few years of relative peace. Biographers have therefore tended to treat it one-sidedly as the first station of her last journey. Poland and the ways of reception of St. Edith Stein in the Polish reality since the 1950s occupy a special place in the paper.